Thermodynamic analysis of autothermal reforming of methane via entropy maximization: Hydrogen production - Souza, Thiago Leandro de (2013)
In this work a thermodynamic analysis of the autothermal reforming (ATR) of methane was performed. Equilibrium calculations employing entropy maximization were performed in a wide range of oxygen to methane mole ratio (O/M), steam to methane ratio (S/ M), inlet temperature (IT), and system pressure (P). The main calculated parameters were hydrogen yield, carbon monoxide formation, methane conversion, coke formation, and equilibrium temperature. Further, the optimum operating oxygen to methane feed ratio that maximizes hydrogen production, at P ¼ 1 bar, has been calculated. The nonlinear programming problem applied to the simultaneous chemical and phase equilibrium calculation was implemented in GAMS, using CONOPT2 solver. The maximum amount of hydrogen obtained was in the order of 3 moles of hydrogen per mole of fed methane at IT ¼ 1000 C, P ¼ 1 bar, S/M ¼ 5, and O/M ¼ 0.18. Experimental literature data are in good agreement with calculation results obtained through proposed methodology.